Предмет: Математика,
автор: pbv123
2(0,3x-2/9)-(-1 1/9+2/3x)=x/5
Ответы
Автор ответа:
0
2( 0,3x - 2/9 ) - ( - 1 1/9 + 2/3x ) = x / 5
0,6x - 4/9 + 1 1/9 - 2/3x = 1/5x
3/5x - 2/3x - 1/5x = 4/9 - 10/9
2/5x - 2/3x = - 2/3
общий знаменатель 15
2x*3 - 2x*5 = - 2*5
6x - 10x = - 10
- 4x = - 10
x = 2,5
0,6x - 4/9 + 1 1/9 - 2/3x = 1/5x
3/5x - 2/3x - 1/5x = 4/9 - 10/9
2/5x - 2/3x = - 2/3
общий знаменатель 15
2x*3 - 2x*5 = - 2*5
6x - 10x = - 10
- 4x = - 10
x = 2,5
Похожие вопросы
Предмет: Українська література,
автор: MelanieQWq
Предмет: Биология,
автор: kislayk24
Предмет: Биология,
автор: mariah22sylim
Предмет: Алгебра,
автор: nekit50rus
Предмет: Алгебра,
автор: danikcool99